I believe I'll go back home : roots and revival in New England folk music - Curren, Thomas S. (Bright Leaf, an imprint of University of Massachusetts Press, 2021)
"Between 1959 and 1968, New England saw a folk revival emerge in more than fifty clubs and coffeehouses, a revolution led by college dropouts, young bohemians, and lovers of traditional music that renewed the work of the region's intellectuals and reformers. From Club 47 in Harvard Square to candlelit venues in Ipswich, Martha's Vineyard, and Amherst, budding musicians and hopeful audiences alike embraced folk music, progressive ideals, and community as alternatives to an increasingly toxic consumer culture. While the Boston-Cambridge Folk Revival was short-lived, the youthful attention that it spurred played a crucial role in the civil rights, world peace, and back-to-the-land movements emerging across the country. Fueled by interviews with key players from the folk music scene, I Believe I'll Go Back Home traces a direct line from Yankee revolutionaries, up-country dancers, and nineteenth-century pacifists to the emergence of blues and rock 'n' roll, ultimately landing at the period of the folk revival. Thomas S. Curren presents the richness and diversity of the New England folk tradition, which continues to provide perspective, inspiration, and healing in the present day"--